Attitudes and knowledge of obesity risks among Male high school students in Al-Madinah, Saudi Arabia - Awad Mohammed Al-Qahtani, Hamza Sundogji (Journal of Applied Pharmaceutical Science, 2016)
The study aimed to evaluate the knowledge about obesity risks and attitude towards obese persons along with prevalence of obesity among high school students in Al-Madinah. This cross-sectional descriptive study included 314 male students enrolled in the secondary schools in Al-Madinah.Multi-stage random sampling technique was applied. Two reliable and valid questionnaires were utilized for data collection; The Obesity Risk knowledge scale (ORK) and Attitude toward Obese Persons (ATOP). Students’ age ranged between 16 and 19 years with a mean of 17.08 years. The prevalence of overweight and obesity were 11.8% and 16.2% respectively. Overall, the knowledge score ranged between 0 and 7. Among 314 students, 241 had insufficient knowledge regarding obesity related issues with just 73 having sufficient knowledge. Students with positive attitude towards obese person were 53.2% whereas 46.8% had negative attitude. There was no association found between student’s age and body mass index (BMI) with their knowledge regarding obesity risks & attitude towards obese person. The study revealed Knowledge of the students regarding obesity risk factors was insufficient whereas their attitude towards obese persons is considered satisfactory along with high prevalence of overweight and obesity among the male adolescent population in Al-Madinah, KSA.
Keywords: Adolescent, Body Mass Index, Obesity risks, Attitudes, Overweight.